O brincar de sujeitos com risco psíquico: um olhar interdisciplinar - Vendruscolo, Josiane Fernanda (2014)
This research analyzes the play of sixteen children between 21 and 26 months showed risk of developing detected between 1 and 18 months by Child Development Risk Inventory proposed research Kupfer (2008 ). To this aime, children were filmed with their relatives in play activities for twenty minutes. The analysis of play was done from three different procedures: a protocol that analyzes the play and communication in a Piagetian cognitive vision ( ZORZI and HAGE , 2004) , another compound by categories proposals from reading transitional object Winnicott (Graña, 2008) and a descriptive analysis of three therapists from different professions, experts in childhood. The results of these analyzes were compared with historical risk children and with each other to check that these distinct analyzes provide data about the necessity of early intervention or another types of intervention indicated by the professionals. The descriptive results from protocols demonstrated that four of the sixteen children were playing, on the cognitive point of view; below expectations for their age group and that, this result was correlated with lower scores on items of the communication protocol, and indicating for language therapy by speech therapists. Two of the four children showed abnormalities in the object relation indicating greater risk of structuring mental disorder. The others children showed no significant changes in the protocols. When, however, analyzed the filming of sixteen children by three experienced professionals (a speech therapist, a psychologist and an occupational therapist), despite the coincident concern with language and psychological development of the four cases indicated by the protocols and the speech therapists, there were also eight other children indicated for early or brief intervention, based on more subtle qualitative changes in playful interaction with the mother. Only four cases were not referred to any intervention. These results demonstrate that the levels of risk for development fulfill the function of early detection of development or psychic risk, since most of the sample developed some kind of trouble, but should not be taken with a diagnostic value. This course can be modified by new spontaneous or even encouraged by occasional interventions familiar postures. Also, suggest that protocols that examine the play from a unique categorical look at the child do not capture the necessary subtleties on play for a more natural reflection to think clinical intervention. They can even detect disturbances in the course of installation, but they do not in all cases. The analysis that favors child - family intersubjectivity in spontaneous play activity, possible from filming, it was a common and preferred shape by the three professionals who analyzed sixteen filming. . They demonstrated that the interface between cognitive, linguistic and psych affective factors was constant and inseparable aspects when asked to analyze the play development. This fact demonstrated that early clinical intervention has to consider these three estrutuctural factors and instrumental one for diagnostic purposes, that is possible from the analysis of play between partners , whether the child and family , or the child and therapist. The three professionals who reviewed the plays sessions highlighted that undergraduate focus on playing is most commonly a cognitive one, and the psycho face became present in postgraduate training. The analyzes performed by therapists, and even the relationships between cognitive and psycho dimensions of play, are well esplanades by Winnicott theory, which enables us to sustain the need to establish a working hypothesis of playing for an every single case.